The effect of a cardiopulmonary bypass system with biocompatible coating on fibrinogen levels determined by the TEG--functional fibrinogen method: preliminary results - Fluger, I; Maderová, K; Simek, M; Hájek, R; Zapletalová, J; Lonsky, V (Perfusion, 2011)
When cardiopulmonary bypass (CPB) is used, the blood comes into contact with foreign surfaces. To diminish this impact, various types of biocompatibly coated surfaces have been developed. The study assessed the effects of heparin-coated CPB systems on the level and function of fibrinogen as measured by thromboelastography (TEG), as compared with non-coated systems. No statistically significant differences between both groups were revealed by comparing paired data. In our study, heparin-coated CPB circuits had no significant effect on either fibrinogen level or its function.
Keywords: fibrinogen; dospělí; Humans; Fibrinogen; lidé středního věku; Middle Aged; Cardiopulmonary Bypass; Heparin; kardiopulmonální bypass; mužské pohlaví; Adult; tromboelastografie; ženské pohlaví; heparin; Thrombelastography; Coated Materials, Biocompatible; lidé; biokompatibilní potahované materiály; Aged; senioři; Male; Female